PECULIARITIES OF DEVELOPMENT OF ECOLOGICAL CULTURE OF HIGH SCHOOL STUDENTS - Nurishev, Darmenbay (Журнал иностранных языков и лингвистики, 2023)
The article describes the importance of bringing the school system to a new level of quality that meets the tasks of modernizing the educational space of today’s modern society. Therefore, as a structural element of the state, the school should be an institution capable of choosing a direction in rapidly changing socio-economic conditions, working independently on the development of private ecological literacy. In the article, it is noted that it would be better to use real-life examples in teaching high school students. Also, the author assumes that conditions should be created for raising a person who thinks about the consequences of the impact on society, nature and people’s health, increasing the level of ecological culture. The article deals with the assumption that it is necessary to create an educational environment organized using special, national values for the success of the process of raising ecological culture among high school students in educational organizations.